INTERNALISASI NILAI PENDIDIKAN RELIGIUS DALAM KEGIATAN KULTURAL TADARUS-DHUHA - Muhamad Rafli; Muslimin Muslimin; Arya Lesmana Putera; Muhammad Riza Fajrul Azhar; Achmad Faisal; M Rizal (Al-Irsyad: Journal of Education Science, 2026)
Islamic education aims to shape students’ character and personality through the internalization of religious values in their daily lives. SMAN 10 implements a Tadarus-Dhuha program to foster students’ religiosity through a series of activities, including collective recitation of shalawat, Qur’anic reading (tadarus), religious talks (tausiah), and congregational Dhuha prayer. This study aims to examine how religious values are internalized through the Tadarus-Dhuha program and reflected in students’ character. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Previous studies have discussed the role of habituation in Dhuha prayer and Qur’anic recitation in character building; however, studies focusing on the internalization of religious values through continuous cultural activities such as Tadarus-Dhuha remain limited. The findings reveal four main aspects: fostering love for the Prophet Muhammad through shalawat, developing the habit of performing Dhuha prayer, encouraging regular Qur’anic reading, and improving discipline in worship. These findings indicate that habituation and direct experience play a significant role in enhancing students’ religiosity. In conclusion, the Tadarus-Dhuha program is effective as a sustainable culture-based model for character education.